2017
DOI: 10.1101/140830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alterations in striato-thalamo-pallidal intrinsic functional connectivity as a prodrome of Parkinson’s disease

Abstract: Although the diagnosis of Parkinson’s disease (PD) remains anchored around the cardinal motor symptoms of bradykinesia, rest tremor, rigidity and postural instability, it is becoming increasingly clear that the clinical phase of the disease is preceded by a long period of neurodegeneration, which is not readily evident in terms of motor dysfunction. The neurobiological mechanisms that underpin this prodromal phase of PD remain poorly understood. Based on converging evidence of basal ganglia (BG) dysfunction in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In keeping with the suggested white matter changes in motor regions of the brain including those surrounding the thalamus in our study, a recent resting-state fMRI study revealed reduced intra-and interhemispheric functional connectivity in a striatothalamo-pallidal network in patients with either isolated hyposmia or isolated RBD. 52 This further corroborates the notion that degenerative changes may be preferentially observed in patients at PD risk with hyposmia (and/or RBD). By including participants with a reduced smell sense into our study we may thus have artificially selected participants that are not only at risk for PD but, more important, are also at risk for a more rapid decline and a higher tendency to more advanced neurodegeneration.…”
Section: Discussionsupporting
confidence: 85%
“…In keeping with the suggested white matter changes in motor regions of the brain including those surrounding the thalamus in our study, a recent resting-state fMRI study revealed reduced intra-and interhemispheric functional connectivity in a striatothalamo-pallidal network in patients with either isolated hyposmia or isolated RBD. 52 This further corroborates the notion that degenerative changes may be preferentially observed in patients at PD risk with hyposmia (and/or RBD). By including participants with a reduced smell sense into our study we may thus have artificially selected participants that are not only at risk for PD but, more important, are also at risk for a more rapid decline and a higher tendency to more advanced neurodegeneration.…”
Section: Discussionsupporting
confidence: 85%
“…35 Promising techniques include 11 C-donepezil PET/CT (cholinergic (parasympathetic) gut innervation), 123 I-metaiodobenzylguanidine scintigraphy (cardiac sympathetic denervation), 36 susceptibility-weighted and neuromelanin-sensitive MRI (dorsal nigral hyperintensity; integrity of pigmented neurons of the locus coeruleus), 11 Cmethylreboxetine PET (noradrenergic nerve terminals originating in the locus coeruleus), structural connectivity and functional MRI (striatal or whole-brain function). 35,[37][38][39] However, for the establishment of prodromal (neuro)imaging markers consensus on specific methods and analyses is needed. 3.…”
Section: Promising Candidate Markersmentioning
confidence: 99%